2019
DOI: 10.30537/sijmb.v6i1.264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corruption on Exchange Rate: Empirical Evidence from Panel Data

Abstract: Purpose- This study examines the economic cost of exchange rate. Pakistan has been facing serious issue in regard of exchange rate and this fluctuations impact on various economic indicators or variables. The overall exchange rate value is being depreciated since 2008, it started from Rs 60 against one dollar and recently it reached to Rs, 134 that are equal to one dollar.  Design/methodology/approach- Time series panel data from 2002-2016 has been used for analysis, it has two cross-sections Pakistan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This is due to both studies using different currencies and samples of data where Hua (2007) uses the renminbi currency while Demir (2010) uses the Lira currency according to each country. The study on corruption also contradicted the results of Bahmani & Nasir (2002), maybe due to different samples of data being more widely consisting of 65 countries and Sohu et al (2019), using different currencies such as Pakistan and Indian rupees.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…This is due to both studies using different currencies and samples of data where Hua (2007) uses the renminbi currency while Demir (2010) uses the Lira currency according to each country. The study on corruption also contradicted the results of Bahmani & Nasir (2002), maybe due to different samples of data being more widely consisting of 65 countries and Sohu et al (2019), using different currencies such as Pakistan and Indian rupees.…”
Section: Resultsmentioning
confidence: 61%
“…Based on the data for corruption rate that is collected from International Country Risk while for productivity is collected from Penn World Table, findings show a country experiencing a high degree of corruption or less law, and order tends to experience a real depreciation in their currency. Moreover, Sohu et. al (2019), study on the impact of corruption on the exchange rate in Pakistan using the time series panel data from the year 2002 until 2016, results show CPI have a significant effect on the real exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Blomberg & Hess (1997) showed that introducing political variables to exchange rate models improves forecasting significantly in comparison to the random walk models. A very recent empirical study by Sohu et al (2019) concluded that the perception of corruption was related to the depreciation of the currencies of India and Pakistan. Kaiser (1997) investigated the impact of news on social expectations as Germany was joining the European Monetary Union.…”
Section: Overviewmentioning
confidence: 99%
“…Intensive research work has been done on measuring brand equity of many sectors like textile, chemical or cement sector but there is less work in measuring the brand equity of cell phone sector in Pakistan because it is emerging and ever improving sector (Sohu et al, 2019). Also, the nature of competition here is of a very severe kind; those companies remain successful here that fulfill customer's needs profitably and with innovative manner.…”
Section: Introductionmentioning
confidence: 99%